Financial Performance, Maqashid Syariah dan Corporate Reputation: Moderasi Islamic Corporate Social Responsibility (ICSR) - Indahyani, Wiwit Siska; Leniwati, Driana; Nugroho Wicaksono, Agung Prasetyo (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2024)
Purpose: This research aims to prove and test empirically how financial performance and Maqashid Syariah impact a company's reputation with Islamic corporate social responsibility (ICSR) as a moderating variable. This study focuses on Sharia Commercial Bank companies registered in Indonesia from 2019 to 2020.Method: This research used a random sample method and took 28 samples from companies over two years. Data analysis uses the panel data regression testing method and the Eviews10 analysis tool.Results: The results of this research show that financial performance has an effect on corporate reputation, and Maqashid Syariah has no effect. Furthermore, Islamic Corporate Social Responsibility can control the relationship between financial performance and corporate reputation, but cannot control the relationship between Maqashid Syariah and corporate reputation.Implications: This research provides implications for the development of accounting science, especially company performance relating to ICSR, and practical contributions in considering ICSR in creating a company reputation.Novelty: The novelty of this research is testing Maqasid Syariah with ICSR as moderation in determining Corporate Reputation with the consideration that the highest form of human responsibility is being responsible to Allah SWT. Therefore, by including Maqashid Syariah and ICSR it will provide novelty in its implications for science and practice.